Peran Komunikasi Costumer Relationship Management dalam Menciptakan Kepuasan Pelanggan di Industri Makanan dan Minuman - Kartika Kartika; Eka Susilawati; Fithrotul Kalimah; Rizqi Fitrianti; Arfian Suryasuciramadhan (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2026)
This study aims to analyze the role of communication in Customer Relationship Management (CRM) systems in creating customer satisfaction at PT Bangkit Jaya Teknik Indonesia, a business-to-business (B2B) cold storage installation service company. The research background lies in the increasing number of customer complaints during 2022–2024, mainly due to delayed responses, suboptimal after-sales service, and the absence of a centralized communication record system. This study employed a qualitative approach with a case study design. Data were collected through observation, semi-structured interviews with internal parties (marketing project, project manager, project PIC) and customers, as well as company archival documentation. The findings reveal that responsive, open, and two-way communication plays a significant role in enhancing customers’ sense of being valued, trust, and loyalty, which ultimately fosters satisfaction. However, communication barriers such as delays in after-sales service, gaps between customer expectations and company procedures, and the lack of a communication database remain major challenges. To overcome these, the company has initiated strategies including the development of a customer communication database, improved after-sales monitoring, and the adjustment of communication standard operating procedures to align with customer needs. These results reinforce the relevance of Relationship Management theory and the IDIC model, both of which emphasize communication as the core of CRM. Theoretically, this study contributes to organizational communication studies, while practically, it provides recommendations for B2B service companies to prioritize communication in CRM strategies to strengthen customer satisfaction and loyalty.